Physical activity and perceived barriers among doctors working in King Abdulaziz Hospital, Jeddah, 2018 - Khateeb, Eyad; AlKharji, Turki; AlQutub, Sulafa (International Journal Of Community Medicine And Public Health, 2019)
Background: Physical inactivity is a major public health problem worldwide, and Saudi Arabia has been identified as one of the countries with the highest prevalence of physical inactivity. This study seeks to determine the physical activity levels and to identify the perceived barriers against physical activity among doctors. Methods: We performed a cross-sectional study involving all physicians practicing in King Abdulaziz Hospital in Jeddah, Saudi Arabia. All doctors holding administrative positions during the conduct of the survey were excluded from the study. Systematic random sampling was used to select the doctors. A previously published and validated self-administered questionnaire was used in the study. The results of the study were analyzed using IBM SPSS version 23. Results: Among the 178 physicians surveyed, more than half (74.6%) reported having regular physical activity. Among the 129 doctors who reported low to high physical activity, 50.0% were in the moderate to high category, meanwhile only 23.7% were in the low category. We found a significant relationship between the level of physical activity and perceived total exercise benefits/barriers (p<0.001), exercise benefits (p-value=0.009), and exercise barriers (p<0.001). Conclusions: Most of the physicians were physically active. However, there is still a need to encourage physicians to improve their physical activity, which would improve their perception of exercise and set them as better role models for physical activity among their patients and the communityz.